Estudo comparativo das madeiras de cecropia palmata (imbaúba) e eucalyptus grandis para produção de celulose e papel - Pupo, Camyla Heckler [UNESP] (2015)
Much remains to be studied on the Amazonian species, among many varieties can be species with excellent characteristics for the production of pulp and paper that have not yet had their technological potential revealed. The Cecropia palmata is native to the Amazon, which initially presents excellent characteristics for pulp production. Therefore, this study aimed to study the quality of the native wood Cecropia palmata Amazon for the production of pulp and paper, through a comparative study with the species E. grandis, in order to provide the production industries a new option fibrous raw material. Were selected 10 trees and determined the dendrometric parameters, basic density and chemical composition (holocellulose, lignin and extractives). In Kraft pulping, required two cooks, (14 and 16% active alkali). With cellulose was determined the yield, reject content, Kappa and specific wood consumption (SWC). The cellulose fibers were classified into Bauer McNett classifier, the morphology the fibers were determined on FQA (Fiber Quality Analyzer), and the pulp was refined in Jokro Mühle centrifugal grinder. Physical and mechanical tests were carried out in refined cellulose papers. C. palmata showed low productivity and high proportion of bark (16.1%), with statistically significant differences in all parameters dendrometric compared with the E. grandis ...